The Role of Farmer Group On Application the Sapta Usahatani Programs Lowland Rice Farming at Bunga Jadi Village, Muara Kaman District, Kutai Kartanegara Regency - Fahrizal Fahmi, Siti Balkis . (Universitas 17 Agustus 1945 Samarinda, 2017)
The purpose of this research was to know of the role of farmers group in the implementation of Sapta Usahatani Programs lowland rice farming by farmers in the Bunga Jadi Village, Muara Kaman District, Kutai Kartanegara Regency. The method sampling that used is proportional stratified random sampling method with the number of respondents 41 families (KK). This research use chi kuadrat (X2) analysis method, who the first variable is he role of farmer groups and the second variable is the level of implementation of Sapta Usahatani programs,Based on the research results, it can be concluded that a group of farmers in Desa Bunga Jadi it has been classified as farmer groups are quite advanced, it is seen from the data obtained both for planning element, the element of dooperation in implementing the plan, as wele as elements of the development and utilization of facilities belonging to the group, initiatives and agreements as well as elements of the groups, already implemented in the high category. Except on the elements of teaching and learning is still in the moderate category. Implementation of the program Sapta Usahatani lowland rice from 7 element have been categorized held on high criteria, namely the use of improved seed, tillage, fertilization, pest and disease control, irrigation, and post harvest handling. Except on the elements of marketing activity results which are still in the moderate category in the village of Bunga Jadi, who X2 count of 11,16 compared with 9,49 X2 table. The results showed that farmers group have role of very effective to the implementation of Sapta Usahatani program lowland rice farming in Bunga Jadi Village.